New tricks of an old enemy: isolates of F usarium graminearum produce a type A trichothecene mycotoxin - Varga, Elisabeth (Environ Microbiol, 2015)
The ubiquitous filamentous fungus F usarium graminearum causes the important disease Fusarium head blight on various species of cereals, leading to contamination of grains with mycotoxins. In a survey of F . graminearum (sensu stricto) on wheat in North America several novel strains were isolated, which produced none of the known trichothecene mycotoxins despite causing normal disease symptoms. In rice cultures, a new trichothecene mycotoxin (named NX‐2) was characterized by liquid chromatography‐tandem mass spectrometry. Nuclear magnetic resonance measurements identified NX‐2 as 3α‐acetoxy‐7α,15‐dihydroxy‐12,13‐epoxytrichothec‐9‐ene. Compared with the well‐known 3‐acetyl‐deoxynivalenol (3‐ADON), it lacks the keto group at C‐8 and hence is a type A trichothecene. Wheat ears inoculated with the isolated strains revealed a 10‐fold higher contamination with its deacetylated form, named NX‐3, (up to 540 mg kg(−1)) compared with NX‐2. The toxicities of the novel mycotoxins were evaluated utilizing two in vitro translation assays and the alga C hlamydomonas reinhardtii. NX‐3 inhibits protein biosynthesis to almost the same extent as the prominent mycotoxin deoxynivalenol, while NX‐2 is far less toxic, similar to 3‐ADON. Genetic analysis revealed a different TRI 1 allele in the N‐isolates, which was verified to be responsible for the difference in hydroxylation at C‐8.